Contact with primary health care physicians before an acute hospitalisation - Lena J. Skarshaug; Ellen R. Svedahl; Johan H. Bjørngaard; Aslak Steinsbekk; Kristine Pape (Taylor & Francis Group, 2019)
Objectives: To assess contacts with general practitioners (GPs), both regular GPs and out-of-hours GP services (OOH) during the year before an emergency hospital admission. Design: Longitudinal design with register-based information on somatic health care contacts and use of municipality health care services. Setting: Four municipalities in central Norway, 2012-2013. Subjects: Inhabitants aged 50 and older admitted to hospital for acute myocardial infarction, hip fracture, stroke, heart failure, or pneumonia. Main outcome measures: GP contact during the year and month before an emergency hospital admission. Results: Among 66,952 identified participants, 720 were admitted to hospital for acute myocardial infarction, 645 for hip fracture, 740 for stroke, 399 for heart failure, and 853 for pneumonia in the two-year study period. The majority of these acutely admitted patients had contact with general practitioners each month before the emergency hospital admission, especially contacts with a regular GP. A general increase in GP contact was observed towards the time of hospital admission, but development differed between the patient groups. Patients admitted with heart failure had the steepest increase of monthly GP contact. A sizable percentage did not contact the regular GP or OOH services the last month before admission, in particular men aged 50-64 admitted with myocardial infarction or stroke. Conclusion: The majority of patients acutely admitted to hospital for different common severe emergency diagnoses have been in contact with GPs during the month and year before the admission. This points towards general practitioners having an important role in these patients' health care.KEY MESSAGES There is scarce knowledge about primary health care contact before an emergency hospital admission. The percentage of patients with contacts differed between patient groups, and increased towards hospital admission for most diagnoses, particularly heart failure. More than 50% having monthly general practitioner contact before admission underscores the general practitioners' role in these patients' health care. Our results underscore the need to consider medical diagnosis when talking about the role of general practitioners in preventing emergency hospital admissions.